Pengaruh Prilaku Kepemimpinan Kepala Sekolah an Motivasi Kerja Guru Terhadap Kinerja Guru di SD Negeri Kecamatan Plaju Palembang - Yeni Maryani; Tri Widayatsih; Nuril Furkan (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the influence of principal leadership behavior and teacher work motivation on teacher performance in public elementary schools (225, 226, 227 Palembang). The benefit of this research's explanation is that it is hoped that it will be able to become a treasure (wealth) of knowledge and knowledge in the world of education, particularly in the efforts of teachers in setting good and quality educational goals for improving teacher performance in public elementary schools (225, 226, and 227 Palembang). The research will take place at Public Elementary Schools 225, 226 and 227 in Palembang. where the research will be carried out from July to October 2022. This quantitative approach is used by researchers to see the contribution of school principal leadership behavior and teacher work motivation to teacher teaching performance. The sample for this study consisted of 78 teachers from Public Elementary Schools 225, 226, and 227. The coefficient of determination (R squared) of multiple regression between the independent variable and the dependent variable is 0.671, as shown in table 4.18 above. This explains that the principal's leadership style and work motivation have a combined effect on teacher performance of 67.1 percent, and the remaining 32.9% of teacher performance is influenced by other factors that were not examined in this study.